Pendidikan Mental melalui Cerita Anak Tindakan Pasca Banjir di SDN Idaman 1 Kecamatan Patia, Pandeglang - Arafat, Yasser (Universitas Mathla'ul Anwar Banten, 2018)
This research is entitled, Mental Education through the Story of Children Acting post Flood in SDN Idaman 1 Kecamatan Patia, Pandeglang Regency, South Banten. Focus First stage of research, namely research based on quantitative data collection and second stage research, namely research that puts forward quantitative and qualitative approaches to deepen the findings of the research results. The measured variables consist of mental education research variables (variable X) and children’s stories (variable Y). The research model used is field observation (direct observation). The research design consists of several stages. The first stage, a quantitative approach with Structural Equation Modeling (SEM) techniques will be used to analyze the relationship between mental education education and children’s stories. The second stage, a qualitative approach with in-depth interview techniques and documentation studies is used to obtain explanations related to literary learning and its implications for character formation in students. Data collection methods consist of structured interviews, read notes, and questionnaire techniques. Data analysis techniques used are descriptive qualitative.